Quantitative culture of endotracheal aspirate and BAL fluid samples in the management of patients with ventilator-associated pneumonia: a randomized clinical trial - Ricardo de Amorim Corrêa; Carlos Michel Luna; José Carlos Fernandez Versiani dos Anjos; Eurípedes Alvarenga Barbosa; Cláudia Juliana de Rezende; Adriano Pereira Rezende; Fernando Henrique Pereira; Manoel Otávio da Costa Rocha (Jornal Brasileiro de Pneumologia, 2014)
OBJECTIVE: To compare 28-day mortality rates and clinical outcomes in ICU patients with ventilator-associated pneumonia according to the diagnostic strategy used. METHODS: This was a prospective randomized clinical trial. Of the 73 patients included in the study, 36 and 37 were randomized to undergo BAL or endotracheal aspiration (EA), respectively. Antibiotic therapy was based on guidelines and was adjusted according to the results of quantitative cultures. RESULTS: The 28-day mortality rate was similar in the BAL and EA groups (25.0% and 37.8%, respectively; p = 0.353). There were no differences between the groups regarding the duration of mechanical ventilation, antibiotic therapy, secondary complications, VAP recurrence, or length of ICU and hospital stay. Initial antibiotic therapy was deemed appropriate in 28 (77.8%) and 30 (83.3%) of the patients in the BAL and EA groups, respectively (p = 0.551). The 28-day mortality rate was not associated with the appropriateness of initial therapy in the BAL and EA groups (appropriate therapy: 35.7% vs. 43.3%; p = 0.553; and inappropriate therapy: 62.5% vs. 50.0%; p = 1.000). Previous use of antibiotics did not affect the culture yield in the EA or BAL group (p = 0.130 and p = 0.484, respectively). CONCLUSIONS: In the context of this study, the management of VAP patients, based on the results of quantitative endotracheal aspirate cultures, led to similar clinical outcomes to those obtained with the results of quantitative BAL fluid cultures.